MENINGKATKAN LOYALITAS PENGUNJUNG MUSEUM KONPERENSI ASIA AFRIKA MELALUI BRAND COMMUNITY SAHABAT MUSEUM (Survei Terhadap Member Sahabat Museum Konperensi Asia Afrika) - Kamilanovy, R. Desny Gita; Fakhrudin, Suwatno (Universitas Pendidikan Indonesia, 2013)
Bandung city to increase tourist arrivals from year to year. It is characterized by several factors such as the products and services of varied tourism, construction of access roads to tourist spots, and increased hotel construction and recreation. Bandung city tourism destinations have varied as culinary tours, shopping, heritage, and educational tours. Educational tours in the city no less a role in the tourism industry, one of which is a museum. One of the interesting tourist attraction in the city of Bandung Asian-African Conference Museum is the reference and study materials by the academic community in terms of the uniqueness of certain aspects of the documentation or the documentation and imaginative thinking in the future, this is done by the museum to maintain the loyalty of its visitors. Therefore the Asian-African Conference Museum visitors maintain loyalty through brand community Friends of the Museum consists of consciousness of kind of kind (brand awareness), rituals and tradition (ritual and tradition), and moral responsibility (feeling of responsibility). Based on the above then do research on brand loyalty is seen from the community. The unit of analysis of this study is the Asian-African Conference Museum visitors as loyal visitors who take the program brand community Friends of the Museum. The method used in this research is descriptive and verification, this study done in less than one year, then the method used is the cross sectional method. The data used are primary data and secondary data through literature study and a questionnaire. To measure the influence of brand community loyalty used multiple regression analysis, the aim of this research to determine the influence of brand community loyalty. Based on the results of the descriptive assessment 100 respondents who obtain the greatest value in the moral community brand responsibility. While the greatest value on the loyalty of the visits between product lines and services. In verifikatif brand community consists of consciousness of kind of kind (brand awareness), rituals and tradition (ritual and tradition), and moral responsibility (feeling of responsibility) may partially affect loyalty, different relations simultaneously based on the results of the analysis that the consciousness of kind have a negative influence on loyalty